Analysis of Waste Water for Bioelectric Generation Using Microbial Fuel Cells - Rawat, Shweta; Rawat, Jyoti (International Journal of Applied Sciences and Biotechnology, 2016)
Microbial fuel cell technology is a recent approach which consist renewable and sustainable technology for electricity generation. Great attentions have been paid to microbial fuel cells (MFCs). Since, it recovers energy from renewable materials that can be difficult to dispose, such as organic wastes, waste water etc. and utilize variety of biodegradable substrates as fuel. Through which, microorganisms actively catabolize substrate and generate electricity. Besides many advantages, it still faces some limitations such as low power and current density. In the present research waste water was physically, biologically and chemically tested. We found that waste water has less amount of toxicity. Thus, it was assumed as low strength waste water and used for the MFC setup for bioelectric generation. Initially, the setup was run three times in a small scale. Simultaneously voltage and current was measured at different time intervals. It was observed that in first run, the voltage and current fluctuation data was not significant but voltage generation was varied from 140.8-182.5 mV in final run, correspondingly current fluctuated from 51-352 μA and power varied from 7180.8-66439.1 nW. However, we got highest power density of 0.0215-0.042 mW when the setup was moved in higher scale. Int J Appl Sci Biotechnol, Vol 4(3): 281-287